2004
DOI: 10.1352/0047-6765(2004)42<136:aposai>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Academic Progress of Students Across Inclusive and Traditional Settings

Abstract: Effects of inclusive school settings for students in six Indiana school corporations were investigated. Results reveal that students without disabilities educated in inclusive settings made significantly greater academic progress in mathematics and reading. For students with disabilities, there were no significant differences in reading and math achievement across the comparison groups. However, a review of group means and the percentage of students making comparable or greater than average academic progress w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(97 citation statements)
references
References 8 publications
6
83
0
8
Order By: Relevance
“…Evidence also indicates that students with and without disabilities who are educated in inclusive classrooms have better academic outcomes than students who are educated in noninclusive classrooms. For example, several studies have shown that students without disabilities make significantly greater progress in reading and math when taught in an inclusive setting with students with disabilities (Cole, Waldron, & Majd, 2004;Cosier, Causton-Theoharis, & Theoharis, 2013).…”
Section: Myth 1 Inclusive Education Will Have a Negative Impact On Smentioning
confidence: 99%
“…Evidence also indicates that students with and without disabilities who are educated in inclusive classrooms have better academic outcomes than students who are educated in noninclusive classrooms. For example, several studies have shown that students without disabilities make significantly greater progress in reading and math when taught in an inclusive setting with students with disabilities (Cole, Waldron, & Majd, 2004;Cosier, Causton-Theoharis, & Theoharis, 2013).…”
Section: Myth 1 Inclusive Education Will Have a Negative Impact On Smentioning
confidence: 99%
“…The results from the current study concur with prior research in that inclusion supports the academic growth and success of students in the general setting (Cole, Waldron, & Majd, 2004;Garriott, Miller, & Snyder, 2003;Rea, McLaughlin, & WaltherThomas, 2002), but only when teachers provide instructional strategies that are known to support academic achievement for children with disabilities (Bender, Vail, & Scott, 1995). Moreover, Freeman and Aikin (2000) further add that full inclusion does benefit students with disabilities academically rather than partial integration.…”
Section: Research Questionsupporting
confidence: 87%
“…Early reports provided evidence that the conventional methods of teaching students with disabilities (i.e., resource rooms) could not continue (Will, 1986a), and exclusion from the regular setting contributed a detrimental effect on a child's social and academic growth (Cole, Waldron, & Majd, 2004;Crossley, 2000).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Así, existen algunos estudios que demuestran los efectos positivos de la educación inclusiva en alumnos con discapacidades graves y permanentes: Rafferty, Piscitelli y Boettcher (2003) o Bunch (2008) señalan la incidencia positiva del ambiente inclusivo en el proceso de aprendizaje del alumnado con discapacidad severa y, de igual modo, otros autores como Cole, Waldron y Majd (2004), Myklebust (2007) o Ruijs y Peetsma (2009) revelan cómo la motivación y los resultados académicos del alumnado con discapacidad aumentan en este tipo de contextos.…”
Section: Introductionunclassified